Analisis Empiris Faktor-Faktor Kunci Penentu Keselamatan Pelayaran: Studi Kasus: Implementasi Manajemen di Pelabuhan Gresik - Nur’aini Budi Cahyani; Retno Mulatsih; Andar Sri Sumantri (Port Management and Maritime Administration Journal, 2025)
Shipping safety is an essential prerequisite in global and domestic maritime operations. However, ship accident incidents remain an annual vulnerability, often caused by suboptimal safety systems. This study aims to analyze the partial effects of the Implementation of the International Safety Management (ISM) Code (X1), the Implementation of Shipping Navigation Aids (SBNP) (X2), Master's Responsibility (X3), and Crewing (X4) on Shipping Safety (Y) at Gresik Public Port, East Jawa. The method used is descriptive and quantitative analysis with multiple linear regression. The research population consists of ship crew members at Gresik Port, with a sample of 100 respondents selected through the Quota Sampling technique. The results of the regression analysis show the equation Y = -1.480 + 0.293X1 + 0.314X2 + 0.187X3 + 0.311X4 + μ. The partial hypothesis test (t-test) confirms that all independent variables have a positive and significant effect on Shipping Safety. The most dominant variable influencing Shipping Safety is SBNP Implementation (X2) with a coefficient of 0.314, followed closely by Crewing (X4) with a coefficient of 0.311. The Coefficient of Determination (R^2) is 0.685, indicating that 68.5% of the variation in Shipping Safety is influenced by these four variables. These findings underscore the importance of investing in technology-based navigation infrastructure and enhancing the competence of maritime human resources in high-traffic operational areas.